Association between weekly fruit and vegetable consumption and depressive symptoms: results from the Korean Elderly Environmental Panel study - Youjeong Yuk; Chae-Rin Han; Yoonyoung Jang; Yun-Chul Hong; Yoon-Jung Choi (Epidemiology and Health, 2021)
OBJECTIVES Although previous studies have investigated the correlation between fruit and vegetable consumption and depression, the results remain inconclusive. The present study aimed to investigate the association between weekly fruit and vegetable consumption and depressive symptoms in elderly Koreans. METHODS A multiple covariate linear regression analysis was performed using the data of 1,226 elderly individuals ≥ 60 years of age who participated in the Korean Elderly Environmental Panel II study from 2012 to 2014. Depressive symptoms were evaluated using the Korean version of the Short form Geriatric Depression Scale (SGDS-K). Generalized linear mixed-effects models were constructed to analyze the repeated measurements of 305 people who participated in the survey every year. RESULTS After adjusting for confounders, SGDS-K scores were negatively associated with the frequency of weekly fruit consumption as follows (β [95% confidence interval; CI]: -0.17 [-0.28 to -0.05], -0.17 [-0.27 to -0.07], -0.42 [-0.54 to 0.29], and -0.33 [-0.44 to -0.21]) for less than 1 time/wk, 1-3 times/wk, 4-6 times/wk, and daily, respectively, compared to no consumption. The SGDS-K scores were also negatively associated with the frequency of vegetable consumption (β [95% CI]: -0.86 [-1.18 to -0.55], -0.18 [-0.35 to -0.01], -0.36 [-0.53 to -0.18], and -0.15 [-0.29 to 0.00]) in the above order, respectively. CONCLUSIONS Fruit consumption was inversely associated with depression levels in a dose-dependent manner. Although there was no dose-response relationship between vegetable consumption and the level of depression, it was negatively associated with SGDS-K scores.